Chronic ectopic pregnancy complicated by septicemic shock and disseminated intravascular coagulation - Sharma, Mamta; ., Rajkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Disseminated intravascular coagulation is a life threatening complication of ectopic pregnancy. It results from washing out of all important procoagulants. This is basically a state of increased propensity for clot formation triggered by a variety of stimuli related to such diverse disorders as sepsis ,endothelial cell damage (heat stroke and shock), obstetrical complication (abruptio placenta, amniotic fluid embolism, severe preeclampsia and retained intrauterine dead foetus). A case of disseminated intravascular coagulation with septicemic shock following laprotomy for ectopic pregnancy is reported. She was treated by vasopressors, broad spectrum antibiotic and aggressive blood and blood component therapy.